Medicated sex in Britain: evidence from the third National Survey of Sexual Attitudes and Lifestyles. (19th June 2015) - Mitchell, Kirstin R; Prah, Philip; Mercer, Catherine H; Datta, Jessica; Tanton, Clare; Macdowall, Wendy; Copas, Andrew J; Clifton, Soazig; Sonnenberg, Pam; Field, Nigel; Johnson, Anne M; Wellings, Kaye
Abstract : Objectives: To describe the prevalence of medication use to assist sexual performance in Britain and to identify associated factors. Methods: Cross-sectional probability sample, undertaken in 2010–2012, of 15 162 people aged 16–74 years, resident in Britain, of whom, 5617 men and 8095 women reported sexual experience (ever) and 4817 men were sexually-active (reported sex in the last year). Results: Ever use of medication to assist sexual performance (medicated sex) was more commonly reported by men than women (12.9% (95% CI 11.9% to 13.9%) vs 1.9% (95% CI 1.7% to 2.3%)) and associated with older age in men and younger age in women. It was associated with reporting smoking, and use of alcohol and recreational drugs, as well as unsafe sex (≥2 partners and no condom use in the last year) in both men and women. Among men, the proportion reporting medicated sex in the last year was higher among those reporting erectile difficulties (ED) than those not doing so (28.4% (95% CI 24.4% to 32.8%) vs 4.1% (95% CI 3.4% to 4.9%)). In all men, medicated sex was associated with more frequent sexual activity, meeting a partner on the internet, unsafe sex and recent sexually transmitted infections diagnosis; associations that persisted after adjusting for same-sex behaviour and ED. However, there were significant interactions with reporting ED, indicating that among men with ED, medicated sex is not associated with same-sex behaviour and ever use of recreational drugs. Conclusions: A substantial minority of people in Britain report medicated sex, and the association between medicated sex and risky sexual behaviour is not confined to high-risk groups.